PENGARUH KETIADAAN ALAT RADIOLOGI MAGNETIC RESONANCE IMAGING (MRI) PADA BERBAGAI JENIS TERAPI DI RSUD SUMBAWA DITINJAU DARI ASPEK OPERASIONAL - Sapta Dwi Rosadi; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
The results of the correlation analysis indicate that the absence of MRI significantly impacts various types of treatment, such as neurology, orthopedics, cancer, and post-surgical rehabilitation. The relationship between healthcare professionals' perceptions and therapeutic effects is strong and statistically significant. However, the results of the linear regression test showed that the model was not statistically significant (p = 0.886), indicating that the relationship cannot be explained linearly and may involve other variables not yet examined in this model. Nevertheless, from a substantive and practical perspective, this study successfully demonstrates that the absence of MRI significantly impacts the quality and continuity of therapy at Sumbawa Regional General Hospital, and emphasizes the importance of procuring this equipment to improve hospital services.